Corneal perforation associated with ocular graft-versus-host disease - Xu, Yue; Wang, Ying-Ming; Sun, Zheng-Tai; Yang, Xiao-Long; Zhuang, Xin-Yu; Ren, Ya-Ru; Chen, Ying-Jie; Chen, Feng; Ma, Xiao; Tang, Xiao-Wen; Zhang, Xiao-Feng (Frontiers in Oncology, 2022)
Corneal perforation is a rare and serious complication of ocular graft-versus-host disease (oGVHD) patients. This study was to retrospectively report seven corneal perforation patients after allogeneic hematopoietic stem cell transplantation (HSCT). Demographic, hematologic, and ophthalmological data of patients were clarified in detail. Nine eyes of seven corneal perforation patients were clarified (Cases 3 and 6 were bilateral and the others are unilateral). All the cases had other affected GVHD organs, especially skin involvement. The duration between HSCT and corneal perforation was usually long with 21 (17–145) months as median interval, whereas the duration between oGVHD diagnosis and corneal perforation was relatively shorter with 4 (2–81) months as median interval. Most patients presented to ophthalmology department with poor visual acuity, BUT and Schirmer’s test. Eyelid marginal hyperemia and irregularity were observed in most corneal perforation eyes. Keratoplasty or conjunctival flap covering (CFC) surgeries was performed after corneal perforation. After a long-term follow-up for most patients (median 21 months, range: 2–86 months), only two eyes of two patients (22.22%) had a final BCVA of 20/100 or better. Patients involved in both cutaneous GVHD and blepharitis indicate the aggressive development of oGVHD. Early diagnosis, long-term follow-up, and effective multi-disciplinary treatments for oGVHD patients are essential. Corticosteroids and immunosuppressor remain essential, whereas the use of topical corticosteroids should be carefully considered in corneal ulceration patients. In addition, appropriate surgeries should be performed to control oGVHD development in time.